This book is not good for you - Bosch, Pseudonymous. (Bosch, Pseudonymous. Secret series ;, 2009)
Cass's mom is kidnapped by the evil dessert chef, Señor Hugo, who requests the legendary tuning fork as ransom, leading Cass and Max-Ernest to try finding the magical instrument in time.